The murmuring stories of the priestly school : a retrieval of ancient sacerdotal lore - Frankel, David, 1961- (Supplements to Vetus Testamentum, 2002)
This book deals with the stories of Israelite complaint or murmuring in the wilderness found in the books of Exodus and Numbers that were composed and edited by the priesthood of ancient Israel. It discusses the significance of the theme of rebellion and complaint for the ancient priests and analyses the part they played in the development of the theme in the Pentateuch. After a general introduction on the theme of murmuring and on the Priestly School, the book goes on to analyze four major priestly texts: the manna story (Exodus 16); the story of the Scouts (Numbers 13-14); the story of the rebellions surrounding the figure of Korah (Numbers 16-17) and the story of the Waters of Merivah (Numbers 20). The significance of the book is two-fold. First, it develops a methodology that allows one to discriminate between early priestly narrative materials and later priestly editorial supplementation. Second, the work demonstrates the antiquity of the priestly narrative lore in the Pentateuch and the significant role which the priests played in creating and developing major narrative traditions in ancient Israel.